The Construction of History in the Folds of Family History in the Novel Song Lost in West Buenos Aires by María Rosa Lojo - Zulema Moret (Studies in 20th & 21st Century Literature, 2002)
The novels written by María Rosa Lojo strongly reflect a specific preoccupation with the rewriting of history from new perspectives that are related to so-called postmodernism. This is the case with Canción perdida en Buenos Aires al Oeste (1987). This work attempts to articulate a reading of the "private" at a crossroads with the history of the country and of other countries (Argentina/Spain). It is a novel of exiles, from the exile of the Neira family from the Franco dictatorship in the forties to the particular exiles of each family member during the seventies and eighties in Argentina. From the fabric woven of the protagonists' subjectivities, the history of horror of this decade emerges: the Malvinas/Falkland Island War, the disappeared, that which "cannot be spoken." To carry out this ambitious narrative, each character, each voice unfolds through a series of strategies linked to constructions of the "self": letters, diaries and recordings.
Keywords: history; Argentine history; María Rosa Lojo; Canción perdida en Buenos Aires al Oeste; private; Spain; Franco dictatorship; Malvinas/Falkland Island War; los desaparecidos; the disappeared; self; diary; recordings; letters